Mampostería confinada vs pórticos de hormigón: Selección de alternativas para viviendas por esfuerzos propios en Cuba. - Franco Rojas, Yadila; González Díaz, Liliana; Milanes, Celene B.; Félix López, Nelson Saint; Calderín Mestre, Francisco (Revista: Módulo Arquitectura CUC)
60% of the houses in Santiago de Cuba are executed by their own means. Structures with reinforced concrete frames prevail where seismic-resistant design requirements are violated, increasing the seismic vulnerability of the territory. In this investigation, the structural system of confined masonry load-bearing walls, little used in Cuba, was evaluated. In addition, to enable the use of local materials available to the population, can provide adequate behavior in the face of seismic action. As a result, two variants of houses designed with reinforced concrete frame structures and confined masonry loadbearing walls were compared, using the Cuban standard NC 207, 2019 and the Mexican standard NTCM, 2020, respectively. It is shown that, although both variants guarantee an adequate seismic behavior, in the structure of confined masonry load-bearing walls, costs are reduced by 46%. This aspect evidencing its technical and economic feasibility as a conclusion.